Performance management practices and their influence on employees’ job satisfaction - Huseynova, Gunel (My University, 2026)
This research examines the impact of performance management strategies on employee satisfaction levels in current digital and hybrid work environments. Most businesses today employ continuous, technology-based performance systems. However, those updates have frequently resulted in no improvement in employee performance. In fact, there is often a discrepancy between the way performance is evaluated vs. the level at which employees are satisfied with their work. This study details that gap through a review of scholarly literature between 2020 and 2026 and considers how strategies such as continuous feedback, outcome-based evaluation, and technology- driven monitoring impact employee perceptions of these strategies. Social Exchange Theory and the Job Demands -Resources model guide this study. They illustrate how the implementation of these strategies can both increase and detract from job satisfaction based on the manner, in which they are employed. On the subject of performance management, it has been demonstrated that performance management may positively or negatively impact employee job satisfaction. To the extent that employees perceive performance management systems as being supportive and equitable, they experience a greater level of job satisfaction and engagement. Conversely, when performance management systems are perceived to be controlling or monitoring employees, trust is diminished, and employee stress is increased. The research has also identified a number of conceptual gaps in the current body of research on performance management. These areas of future research, especially as they relate to the role of technology, transparency, and hybrid work situations, are particularly pronounced. Overall, the research demonstrates that improving employee job satisfaction will require that organizations shift from performance management systems that are purely transactional to systems that are more relationship-based and employee- focused. Additionally, the current research offers insight into future research directions, along with the need for organizations and employees to balance their respective organizational objectives with their respective employee welfare objectives.
Keywords: performance management practices; employee job satisfaction; human resource management; hybrid work environment